Recycling Agricultural Waste in Iraq and Ways to Benefit from it Economically - Al-Thamir, Samira Nema Kamil (Advances in Social Sciences Research Journal, 2025)
The research was conducted with the aim of shedding light on the volume of annual waste and the large losses that occur as a result of wasting enormous national wealth, most of which are neglected or burned as a result of not adopting a wise policy in the exploitation of these resources. The quantities of lignocellulosic materials were estimated for the agricultural wastes of the most important crops, as well as the orchards and reeds being the most important and widespread annual plants, The approved national and international data were adopted in calculating the per capita consumption rate of cellulosic industries and compressed boards, and then Iraq’s need in the light of international rates, The research proved that there are about (20) million tons annually of lignocellulosic materials in Iraq, at the least estimates, of which only a small part is used, The results of the research indicated that Iraq's annual consumption of paper exceeds (2) million tons, and its consumption of compressed boards is more than one million tons, based on global consumption rates, The results also showed that the annual costs of importing paper (calculated on the basis of the global consumption rate) exceed (1.5) billion dollars, and these combined with other products can exceed the costs of importing (2.5) billion dollars. The research came out with a set of conclusions and recommendations to the concerned authorities to adopt various projects. To exploit these forgotten resources in places provided by beginners with grain crop residues.